An endoscopic-assisted contralateral paramedian supracerebellar infratentorial approach in the treatment of thalamic hemorrhage with hematoma extension into the brainstem: a case report - Sun, Eryi; Lu, Siyuan; Chen, Bo; Wu, Qi (Frontiers in Surgery, 2023)
Objective: Thalamic hemorrhage (TH) with hematoma extension into the brainstem can lead to poor outcomes. In this study, we discussed the feasibility of the endoscopic-assisted contralateral paramedian supracerebellar infratentorial (SCIT) approache as a therapeutic method for treating such patients.Case presentation: A patient suffered from sudden loss of consciousness and right limb weakness, and CT scan indicated TH with hematoma extension into the brainstem. She accepted the surgery of endoscopic-assisted contralateral paramedian SCIT approach.Results: The patient now can open her eyes on her own and move her left arm in response to commands.The endoscopic-assisted contralateral paramedian SCIT approache may be a therapeutic method for treating TH patients with hematoma extension into the brainstem.